2017
DOI: 10.1080/17425247.2018.1378642
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal delivery of stem cell-based therapies for the treatment of brain malignancies

Abstract: Introduction Glioblastoma (GBM) is the most aggressive malignant brain cancer in adults, and its poor prognosis and resistance to the existing standard of care require the development of innovative therapeutic modalities. The local delivery of stem cells as therapeutic carriers against glioma has produced encouraging results, but encounters obstacles with regards to the repeatability and invasiveness of administration. Intranasal delivery of therapeutic stem cells could overcome these obstacles, among others, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 124 publications
(123 reference statements)
0
29
0
Order By: Relevance
“…SPECT imaging has the added benefit of a lower false-positive signaling compared to MRI. 27,183 Near-infrared (NIR) fluorescence imaging is advantageous over conventional fluorescence imaging due to its improved ability to penetrate tissues. NIR fluorescence imaging was shown to visualize and track the in vivo tumor-targeting process and tissue distribution of intravenously injected MSCs.…”
Section: Stem Cell Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…SPECT imaging has the added benefit of a lower false-positive signaling compared to MRI. 27,183 Near-infrared (NIR) fluorescence imaging is advantageous over conventional fluorescence imaging due to its improved ability to penetrate tissues. NIR fluorescence imaging was shown to visualize and track the in vivo tumor-targeting process and tissue distribution of intravenously injected MSCs.…”
Section: Stem Cell Trackingmentioning
confidence: 99%
“…However, they do not provide anatomical information and must be used in conjunction with MRI, computerized tomography, or X-ray. SPECT imaging has the added benefit of a lower false-positive signaling compared to MRI [ 27 , 183 ].…”
Section: Stem Cell Trackingmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ or intravenous injection of naked mitochondria isolated from healthy cells has successfully restored mitochondrial function, with subsequent improvement of mobility in neurotoxin-induced rat models of PD [8,9], but the feasibility and e cacy of intranasal adminstration of mitochondria, a relatively fast, safe approach are unknown. However, studies have demonstrated that stem cells delivered intranasally entered the CNS [10] and have been used in treatment of PD [11] and malignant brain tumours [12].…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal route is conside red as an alternative way. This route has a number of advantages: BBB ceases to be an obstacle, the method is noninvasive and is easily repeatable [15,16]. This study was aimed to investigate the effect of intranasally delivered TLR3 agonist Larifan on microglial cell metabolic profile in rats with C6 glioma.…”
mentioning
confidence: 99%